Human stem cell-derived retinal epithelial cells activate complement via collectin 11 in response to stress. Issue 1 (December 2017) - Fanelli, Giorgia; Gonzalez-Cordero, Anai; Gardner, Peter; Peng, Qi; Fernando, Milan; Kloc, Magdalena; Farrar, Conrad; Naeem, Arifa; Garred, Peter; Ali, Robin; Sacks, Steven
Abstract Age-related macular degeneration (AMD) is a major cause of blindness and is associated with complement dysregulation. The disease is a potential target for stem cell therapy but success is likely to be limited by the inflammatory response. We investigated the innate immune properties of human induced-pluripotent stem cell (iPSC)-derived RPE cells, particularly with regard to the complement pathway. We focused on collectin-11 (CL-11), a pattern recognition molecule that can trigger complement activation in renal epithelial tissue. We found evidence of constitutive and hypoxia-induced expression of CL-11 in iPS-RPE cells, and in the extracellular fluid. Complement activation on the cell surface occurred in conjunction with CL-11 binding. CL-11 has been shown to activate inflammatory responses through recognition of L-fucose, which we confirmed by showing that fucosidase-treated cells, largely, failed to activate complement. The presence of CL-11 in healthy murine and human retinal tissues confirmed the biological relevance of CL-11. Our data describe a new trigger mechanism of complement activation that could be important in disease pathogenesis and therapeutic interventions.